A bibliometric analysis and complied dataset of natural disasters on the Qinghai-Tibet Plateau since 1900 - Jiawei Yi; Xinning Fan; Yunyan Du; Chunhuan Zhang; Sheng Huang; Rui Xu; Xiaoyue Wang; Dingchen Hu; Minglei Lu; Zhenbo Wang (Geomatics, Natural Hazards & Risk)
The Qinghai-Tibet Plateau (QTP) is prone to various types of natural disasters with extensive distribution and severe impacts. A systematic review of historical disasters and their spatiotemporal patterns on the QTP over the past century is crucial for a comprehensive understanding and assessment of disaster risks. By searching research articles on QTP disasters through the Web of Science Core Collection, Scopus, and Chinese Science Citation Database, this study collected 261 papers and conducted a bibliometric analysis to summarize the main disaster types and distribution patterns. We categorized QTP disasters into five major types (geological disasters, glacial disasters, meteorological disasters, hydrological disasters, and other disasters) and 15 subtypes. Furthermore, by integrating data from open platforms, published chronicles, yearbooks, and articles, we compiled a structured dataset of major recorded disaster events on the QTP in the past century, which documents the time, location, intensity, casualties, and direct economic losses of each event. This comprehensive, long-term dataset of QTP disasters surpasses existing open data in temporal coverage and completeness. The dataset will serve as a fundamental resource for disaster research, risk assessment, and prevention planning in the QTP region.